Magnetic nanocolloidal adsorbent and its application in offshore oil spill treatment
By designing magnetic nanocolloid adsorbents, and utilizing ferrite-type composite magnetic nanoparticles and amphiphilic bio-based colloidal networks, the problem of decreased interfacial film stability and magnetic response in marine oil spill treatment of lubricating oils was solved, achieving efficient adsorption, demulsification, and rapid recovery, adapting to complex marine environments.
Patent Information
- Application Number
- CN202611421760.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-11-06
AI Technical Summary
Existing materials for treating marine oil spills of lubricating oil suffer from poor interfacial film stability, insufficient adsorption and penetration, decreased magnetic response after loading, and poor adaptability to the seawater environment. There is a lack of functional materials that combine interfacial demulsification, oil phase enrichment, lubricating oil recombination and decomposition, and high magnetic response recovery capabilities.
A magnetic nanocolloid adsorbent is used, which consists of ferrite-type composite magnetic nanoparticles and an amphiphilic bio-based colloidal network. It is formed through in-situ polymerization or blending and cross-linking, and combines hydrophobic grafted polymers and bio-based polymers to construct dynamic reversible bonds, thereby enhancing the adaptability and self-healing ability of the seawater environment. It utilizes the oxygen vacancies and coordination unsaturated sites on the surface of the magnetic nanocores for coordination adsorption, thereby disrupting the interfacial film and promoting oil droplet aggregation.
It effectively disrupts the lubricating oil-seawater interface film, increases the adsorption rate and saturated adsorption capacity, reduces oil phase viscosity, maintains high magnetic response capability, enables rapid recovery under low magnetic field conditions, adapts to complex marine environments, and is green and sustainable.
Smart Images

Figure CN123038792A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of marine pollution emergency treatment and functional composite materials technology, and relates to a magnetic nanocolloid adsorbent and its application in marine oil spill treatment. Background Technology
[0002] With the rapid development of the global oil industry and the increasing prosperity of maritime shipping, marine oil spills are frequent, posing a serious threat to marine ecosystems, coastal economies, and human health. Persistent toxic substances in oil, such as polycyclic aromatic hydrocarbons (PAHs) and benzo[a]pyrene, can remain in marine ecosystems for extended periods and accumulate through the food chain, exerting significant toxic effects on fish, crustaceans, and plankton, leading to aquatic mortality, abnormal larval development, and population imbalances. Simultaneously, oil spills severely impact coastal fisheries, aquaculture, and coastal tourism, causing enormous economic losses. Therefore, the efficient management of marine oil spill pollution has become an important research direction in the field of environmental protection.
[0003] Currently, marine oil spill remediation technologies mainly include mechanical recovery, chemical dispersion, and in-situ combustion. Mechanical recovery relies on equipment such as oil booms and skimmers, and is greatly affected by sea conditions, waves, and oil film thickness, with limited efficiency in treating thin oil films and dispersed oil droplets. While chemical dispersants can disperse oil spills into tiny droplets, they do not truly remove pollutants and can easily cause potential secondary pollution to the marine ecosystem. In-situ combustion may release large amounts of toxic fumes and residues. In contrast, adsorption methods have received widespread attention due to their simplicity, wide applicability, and lower secondary pollution levels. The core of adsorption lies in the selective adsorption of the oil phase using porous materials with hydrophobic and oleophilic properties, thereby achieving oil-water separation.
[0004] However, existing oil spill adsorption materials still have many problems. On the one hand, some high-performance adsorption materials, such as graphene and MOFs, have high adsorption capacities, but their preparation costs are high and they are difficult to scale up. On the other hand, low-cost materials such as natural fibers and biomass sponges, while environmentally friendly, generally suffer from poor mechanical stability, easy swelling after adsorption, and poor recyclability. In addition, most traditional adsorption materials rely solely on their surface hydrophobic and oleophilic structures to achieve physical adsorption of oil, which can easily lead to decreased adsorption efficiency, difficulties in oil desorption and recovery in complex marine environments.
[0005] Current research on marine oil spill absorbent materials mainly focuses on common oil products such as crude oil, diesel, and fuel oil, while specialized materials for treating lubricating oil spills are relatively few. Compared with common oil products, lubricating oil has significantly different compositional characteristics. Lubricating oil is usually formed by blending base oil with a large number of functional additives, including detergents, dispersants, antioxidants, viscosity index improvers, extreme pressure agents, anti-wear agents, and metal soaps. Furthermore, lubricating oil that has been in long-term service or has undergone thermal oxidative aging is also enriched with oxidation products, gums, asphaltenes-like aggregates, and fine wear particles. These polar and surface-active components readily form stable interfacial films at the oil-water interface and, under seawater disturbance conditions, form stable emulsion systems, giving lubricating oil high viscosity, high interfacial stability, and strong aggregation characteristics.
[0006] Due to the unique interfacial behavior and high viscosity of lubricating oil, traditional hydrophobic adsorbents have significant limitations in treating lubricating oil spills: on the one hand, the presence of a stable interfacial film makes it difficult for the oil phase to quickly enter the material pores, significantly reducing the adsorption rate; on the other hand, gum and asphaltenes-like aggregates easily clog the material pores, leading to a decrease in adsorption capacity; furthermore, after adsorbing a large amount of high-viscosity lubricating oil, the overall mass of the oil-material composite increases rapidly, reducing the proportion of magnetic components per unit mass of the composite, thus weakening the magnetic response and reducing the magnetic recovery efficiency. In low-temperature, high-salinity seawater environments, the fluidity of lubricating oil further decreases, making it even more difficult for existing magnetic adsorbents to simultaneously maintain effective adsorption and rapid recovery.
[0007] Therefore, existing technologies still lack a functional material specifically designed for the characteristics of strong interfacial stability, high emulsification, and high viscosity of lubricating oil spills, and especially lack a magnetic nanocolloid adsorbent that combines interfacial demulsification, oil phase enrichment, lubricating oil recombination and decomposition, and high magnetic response recovery capabilities.
[0008] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a magnetic nanocolloid adsorbent, its preparation method, and its application, thereby solving the problems of interfacial film instability, insufficient adsorption and penetration, decreased magnetic response after loading, and poor adaptability to seawater environment in the case of marine oil spills of lubricating oil.
[0010] To achieve the above objectives, the present invention adopts the following technical solution: A magnetic nanocolloid adsorbent includes a magnetic nanocore and an amphiphilic bio-based colloidal network coated on the surface of the magnetic nanocore.
[0011] The ferrite-type composite magnetic nanoparticles are selected from at least one of Fe3O4 or γ-Fe2O3, and the ferrite-type composite magnetic nanoparticles are doped with at least one metal element selected from Co, Ni, Mn and Cu, and the molar ratio of Fe to the metal element is 95:5 to 90:10. The amphiphilic bio-based colloidal network is formed by in-situ polymerization or blending and cross-linking of bio-based polymers and hydrophobic grafted polymers.
[0012] The bio-based polymer is selected from at least one of chitosan, carboxymethyl cellulose, oxidized cellulose, lignin derivatives, tannic acid derivatives, and starch derivatives.
[0013] The hydrophobic grafted polymer is selected from at least one of acrylate polymers, methacrylate polymers, and polyurethane acrylate polymers containing C8-C18 alkyl side chains.
[0014] The magnetic nanonucleus accounts for 35-70 wt% of the total mass of the magnetic nanocolloid adsorbent, with the remainder being amphiphilic bio-based colloidal components.
[0015] Preferably, the average particle size of the magnetic nanonucleus is 10–80 nm, more preferably 15–50 nm.
[0016] Preferably, the saturation magnetization of the magnetic nanonucleus is 40–180 emu / g.
[0017] Preferably, in the amphiphilic bio-based colloidal network, the mass ratio of the bio-based polymer to the hydrophobic grafted polymer is 100:(10-80).
[0018] Preferably, the amphiphilic bio-based colloidal network comprises at least one dynamically interacting structure selected from Schiff base bonds, hydrogen bonds, and metal coordination bonds.
[0019] By adopting the above technical solution, the Schiff base bond, hydrogen bond or metal coordination bond is a dynamic reversible bond, which can respond to changes in pH, ionic strength or mechanical force in the seawater environment, endowing the colloidal network with self-adaptability and self-repair ability, avoiding structural damage under the impact of wind and waves, and at the same time facilitating the regeneration treatment after the adsorbent is recovered.
[0020] Furthermore, the amphiphilic bio-based colloidal network further comprises an ester crosslinking structure.
[0021] Preferably, in the magnetic nanocolloid adsorbent, the surface of the magnetic nanonucleus has oxygen vacancies and / or coordination unsaturated sites.
[0022] By adopting the above technical solution, the hydrophilic segment of the amphiphilic bio-based colloidal network in this invention can undergo hydrogen bonding or coordination with the active components of the lubricating oil interface, while the hydrophobic segment inserts into the oil phase, thereby disrupting the integrity of the original oil-water interface film and inducing oil droplet aggregation, thus improving adsorption efficiency. At the same time, the oxygen vacancies and coordination unsaturated sites on the surface of the magnetic nanonucleus can undergo strong coordination adsorption with polar aggregates (such as colloids and asphaltenes) in the lubricating oil, weakening the non-covalent bonds (hydrogen bonds, π-π stacking) between aggregates, making them loose and smaller in size, thereby reducing the apparent viscosity of the oil phase and improving the ability of the adsorbent to penetrate into the oil layer. In addition, by using iron-based ferrite cores doped with Co / Ni / Mn / Cu (Fe:M molar ratio 95:5~90:10), combined with the coating and isolation effect of the colloidal network, the material after oil adsorption can still maintain rapid recovery performance under low magnetic field (0.01~0.5T), effectively overcoming the magnetic dilution problem.
[0023] The present invention also provides a method for preparing the magnetic nanocolloid adsorbent, comprising the following steps: S1. Preparation of magnetic nanonuclei: Combine an iron source with at least one of a Co source, Ni source, Mn source, or Cu source, and obtain composite ferrite nanoparticles by at least one of a co-precipitation method, a hydrothermal method, or a solvothermal method. S2. Preparation of colloidal precursor: Bio-based polymers are mixed with hydrophobic grafted polymers, and crosslinking agents and / or initiators are added to form amphiphilic colloidal precursors; S3. Composite molding: The composite ferrite nanoparticles are added to the amphiphilic colloidal precursor, and magnetic nanocolloid composites are formed by in-situ polymerization or blending. S4. Post-processing: The magnetic nanocolloid composite is washed, cured and dried to obtain the magnetic nanocolloid adsorbent.
[0024] Preferably, the iron source in step S1 includes Fe. 2+ Salt and Fe 3+ At least one of the salts, the Fe 2+ Salt and Fe 3+ The salt is selected from at least one of chloride, sulfate, and nitrate; the Co source, Ni source, Mn source, and Cu source are selected from at least one of their corresponding chloride, sulfate, and nitrate.
[0025] Preferably, when the reaction in step S1 is a coprecipitation reaction, the reaction temperature is 70-95℃, the reaction pH is 9.0-11.5, the stirring rate is 300-900 rpm, and the reaction time is 0.5-4 h.
[0026] Preferably, when the reaction in step S1 is a solvothermal reaction, the reaction temperature is 140–220°C and the reaction time is 6–18 h.
[0027] Preferably, during and / or after the formation of the composite ferrite nanoparticles in step S1, the content of oxygen vacancies and / or coordination unsaturated sites on the particle surface is controlled by at least one of the following methods: solvothermal reduction environment, non-stoichiometric ratio of metal ions, low-temperature heat treatment, inert atmosphere treatment, and reducing atmosphere treatment.
[0028] Preferably, in step S2, the bio-based polymer has a mass fraction of 1-8 wt%, the hydrophobic grafted polymer has a mass fraction of 2-20 wt%, the crosslinking agent has a mass fraction of 0.2-5 wt%, and the initiator has a mass fraction of 0.1-2 wt%.
[0029] Preferably, in step S3, the ferrite-type composite magnetic nanoparticles account for 35-60 wt% of the total solid mass of the magnetic nanocolloid adsorbent, and are dispersed under high shear at 500-3000 rpm for 5-30 min.
[0030] Preferably, the in-situ polymerization is carried out at 40–85°C for 1–8 hours; or the blending crosslinking is carried out at 25–70°C for 0.5–6 hours; in-situ polymerization is preferred.
[0031] The present invention also provides the application of the magnetic nanocolloid adsorbent in marine oil spill treatment.
[0032] Preferably, the marine oil spill is a lubricating oil spill, which includes at least one of engine lubricating oil, gear oil, hydraulic oil, marine lubricating oil, and industrial grease spill.
[0033] Preferably, the lubricating oil spill comprises a base oil and an additive system, wherein the additive system includes at least one of detergent-dispersant, antioxidant, extreme pressure agent, anti-wear agent, and metal passivator.
[0034] Preferably, the marine oil spill treatment includes: placing the magnetic nanocolloid adsorbent onto the surface of the oil film to adsorb, demulsify and enrich the lubricating oil, and then using an external magnetic field to aggregate and recover the adsorbed material.
[0035] By adopting the above technical solution and preparation method, the oxygen vacancies and coordination unsaturated sites on the surface of the magnetic nanonuclei in this invention are intentionally introduced through methods such as solvothermal reduction environment, non-stoichiometric control, or low-temperature inert atmosphere heat treatment. These surface defect sites have high surface energy and strong affinity for polar groups, enabling them to undergo coordination adsorption with colloids, oxidation products, and additive decomposition products in lubricating oil in a seawater environment. This disrupts the hydrogen bonds, π-π stacking, and van der Waals force networks between these aggregates, promoting a reduction in aggregate size and a loosening of the spatial structure, thereby reducing oil phase viscosity and flow resistance. This process does not involve the breaking of the covalent backbone but is based on the synergistic effect of interfacial interactions and coordination adsorption according to coordination chemistry and colloidal interface principles; it has advantages such as mild reaction conditions, no secondary pollution, and strong controllability.
[0036] Preferably, the magnetic induction intensity of the external magnetic field is 0.01 to 0.5 T.
[0037] The above technical solution is beneficial to maintaining the high magnetic response of the magnetic core. Since the oil load in the composite after adsorption is large, the proportion of magnetic material in the composite per unit mass will decrease. Therefore, this invention uses a composite ferrite of iron and a small amount of Co / Ni / Mn / Cu to optimize the particle size and surface defects while maintaining a high saturation magnetization. The uniform coating of the colloidal network reduces the agglomeration and oxidation between magnetic cores, so that the apparent magnetization of the composite material per unit mass after oil adsorption still meets the requirements of magnetic recovery.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) Interfacial film disturbance and efficient demulsification: The hydrophilic / hydrophobic synergistic effect in the amphiphilic bio-based colloidal network can effectively destroy the viscoelastic adsorption film on the lubricating oil-seawater interface, promote the coalescence of emulsified oil droplets, and significantly improve the adsorbent's capture rate and saturated adsorption capacity for the oil phase.
[0039] 2) Dispersion and viscosity reduction at the polar aggregate interface: Utilizing oxygen vacancies and unsaturated sites on the surface of the magnetic core, strong coordination adsorption occurs with polar aggregates in the lubricating oil, disrupting the non-covalent bond network between aggregates, reducing oil phase viscosity and yield stress, and improving mass transfer efficiency during adsorption. This effect remains significant even under normal temperature and high-salinity seawater conditions.
[0040] 3) High magnetic response and antimagnetic dilution: By optimizing the ferrite composition (Fe:M molar ratio 95:5~90:10) and particle size (15~50nm), and combining the coating and dispersion effect of the colloidal network, the adsorbent can still rapidly aggregate and recover within 1~30 minutes under a low magnetic field of 0.01~0.5T after adsorbing 3~8 times its own weight of lubricating oil, thus meeting the timeliness requirements of marine oil spill emergency response.
[0041] 4) Excellent adaptability to seawater environment: The hydrophilic groups (-OH, -COOH, -NH2, etc.) in the bio-based colloidal network form a stable hydration layer in the high salinity of seawater, preventing particle aggregation; at the same time, dynamic covalent bonds (Schiff base bonds, hydrogen bonds, metal coordination bonds) can buffer the impact of salt ions on the network structure, giving the material self-adaptability.
[0042] 5) Green and sustainable: Bio-based polymers (chitosan, cellulose, lignin, tannic acid, starch derivatives) are widely available and biodegradable, the amount of hydrophobic grafted chains used is controllable, and the overall environmental impact is low. Attached Figure Description
[0043] Figure 1 A schematic diagram illustrating the structure and working principle of magnetic nanoparticle colloidal adsorbents; Figure 2 The apparent viscosity change curve of the emulsified lubricating oil system after the addition of magnetic nanocolloid adsorbent is shown. Detailed Implementation
[0044] The present invention will be further described below through specific embodiments. To make the inventive objectives, technical solutions, and beneficial technical effects of the present invention clearer, the present invention will be further described in detail below with reference to the embodiments. It should be understood that the embodiments described in this specification are merely for explaining the present invention and are not intended to limit the present invention.
[0045] Unless otherwise stated, all instruments and reagents used in the examples are commercially available or synthesized using conventional methods and can be used directly without further processing, and all instruments used in the examples are commercially available.
[0046] Reagents and Experiments: 1. Lubricating oil adsorption capacity: Take 100 mL of simulated seawater (3.5 wt% NaCl), add 10 mL of marine lubricating oil, stir gently at room temperature to form an oil film, then add 0.20 g of pre-weighed magnetic nanocolloid adsorbent. After standing for 10 min, separate using a magnetic field, remove the adsorbent, weigh it, and calculate the adsorption capacity using the following formula:
[0047] Where m0 is the mass of the dried adsorbent and m1 is the mass after adsorption.
[0048] 2. Demulsification of emulsified lubricating oil: Take 50 mL of lubricating oil / simulated seawater emulsion, in which the mass fraction of lubricating oil is 5 wt%, and emulsify it for 5 min using a high-speed homogenizer at 12000 rpm to obtain a stable emulsion; add 0.10 g of magnetic nanocolloid adsorbent, shake gently for 5 min and let stand for 10 min, record the volume of oil-water separation, and calculate the demulsification rate.
[0049] 3. Rheological viscosity reduction experiment: The emulsion system formed by lubricating oil and simulated seawater was placed in a rotational rheometer to test the change in apparent viscosity before and after sample addition; the amount of adsorbent added was 1 wt% of the total mass of the emulsion, and the viscosity was measured after contact for 10 min, and the viscosity reduction rate was calculated.
[0050] 4. Magnetic recovery experiment: After adsorption is completed, a magnetic field of 0.05T is applied to one side of the sample bottle, the time required for the adsorbent to accumulate to the bottle wall is recorded, and the recovery rate is calculated; repeat the cycle 5 times to evaluate the reusability.
[0051] Example 1:
[0052] This embodiment describes the preparation of a magnetic nanocolloid adsorbent for the adsorption, demulsification, enrichment, and magnetic recovery of lubricating oil spills at sea. The embodiment uses a ferrite-type composite magnetic nanonucleus as the main body and an amphiphilic bio-based colloidal network as the carrier. The magnetic nanonucleus is prepared by co-precipitation, and the content of oxygen vacancies and / or coordination unsaturated sites on the particle surface is controlled by low-temperature heat treatment. Subsequently, an amphiphilic bio-based colloidal network is constructed by in-situ polymerization, ultimately yielding the magnetic nanocolloid adsorbent.
[0053] S1. Preparation of magnetic nanonuclei Weigh out 5.14 g of ferric chloride hexahydrate, 2.64 g of ferrous sulfate heptahydrate, and 0.36 g of nickel chloride hexahydrate, and dissolve them separately in 200 mL of deionized water to obtain a mixed metal salt solution. The molar ratio of iron to nickel is 95:5. Then, place the solution in a three-necked flask and heat to 85 °C under nitrogen protection. Stir mechanically at 500 rpm while simultaneously adding 25 wt% ammonia solution to adjust the pH to 10.5. Maintain the reaction at 85 °C and pH 10.5 for 90 min. During the reaction, a black precipitate gradually forms.
[0054] After the reaction was completed, the precipitate was separated using an external magnetic field and washed three times with deionized water and anhydrous ethanol to remove residual salts and free ions. Then, it was vacuum dried at 60°C for 12 hours to obtain preliminary magnetic nanoparticles.
[0055] To further regulate the content of oxygen vacancies and / or coordination unsaturated sites on the surface of the composite ferrite nanoparticles, the obtained magnetic nanoparticles were placed in a tube furnace and heat-treated at 200°C for 2 hours under a nitrogen atmosphere at a heating rate of 2°C / min. After cooling to room temperature, the nanoparticles were removed to obtain ferrite-type composite magnetic nanoparticles.
[0056] S2. Preparation of colloidal precursors Weigh 3.0 g of chitosan and add it to 100 mL of a 2% (w / w) aqueous solution of acetic acid. Stir at 50 °C for 2 h until completely dissolved to obtain a chitosan solution. Separately weigh 2.0 g of carboxymethyl cellulose and add it to 100 mL of deionized water. Stir at 50 °C for 1 h to obtain a carboxymethyl cellulose solution. Combine the two solutions and continue stirring for 30 min to form a bio-based polymer mixed solution.
[0057] Subsequently, hydrophobic grafted monomers were added, with lauryl methacrylate and methyl methacrylate in a mass ratio of 7:3, totaling 40 wt% of the total bio-based polymer mass. Next, N,N'-methylenebisacrylamide, a crosslinking agent, was added at 0.8 wt% of the total monomer mass; an initiator of ammonium persulfate / sodium bisulfite redox initiation system was added, with an ammonium persulfate to sodium bisulfite mass ratio of 1:(0.5–1.5). Premixing was continued at 60 °C for 20 min to obtain the amphiphilic colloidal precursor.
[0058] S3, Composite Molding The ferrite-type composite magnetic nanoparticles obtained in S1 (5.73 g) were added to the amphiphilic colloidal precursor obtained in S2, so that the magnetic nanonuclei accounted for 45 wt% of the total solid mass of the magnetic nanocolloid composite, with the remainder being amphiphilic bio-based colloidal components. After addition, the mixture was dispersed under high shear at 2500 rpm for 15 min to ensure that the magnetic nanonuclei were uniformly dispersed in the colloidal precursor.
[0059] Subsequently, under nitrogen protection, the system was heated to 75°C for in-situ polymerization for 4 hours. During the polymerization process, lauryl methacrylate and methyl methacrylate formed hydrophobic grafted polymer segments, which, together with chitosan / carboxymethyl cellulose, constructed an amphiphilic bio-based colloidal network. The resulting amphiphilic bio-based colloidal network includes hydrogen bonds, hydrophobic association, molecular chain entanglement, and covalent cross-linking structures introduced by cross-linking agents, forming a stable magnetic nanocolloid complex.
[0060] S4, Post-processing The above magnetic nanocolloid composite was washed three times with an ethanol / water mixture to remove residual monomers, initiators and free low-molecular-weight substances; then it was vacuum dried at 50°C for 12 hours to obtain the final magnetic nanocolloid adsorbent.
[0061] Results and Performance Tests showed that the obtained material was in the form of uniform dark brown colloidal particles with a narrow particle size distribution; its magnetic nanonuclei had an average particle size of 32 nm and a saturation magnetization of about 86 emu / g.
[0062] When this material was used to simulate marine lubricating oil spill treatment, it spread rapidly on the oil film surface, disturbing the interfacial active components in the lubricating oil. It also exhibits coordination adsorption and interfacial loosening effects on gums, oxidation products, and asphaltenes-like aggregates, leading to a decrease in local oil viscosity and enhanced oil droplet aggregation. Subsequently, it can be rapidly aggregated and recovered under a 0.05T external magnetic field, indicating that it possesses both good adsorption and magnetic recovery properties.
[0063] Example 2:
[0064] This embodiment is used to prepare a magnetic nanocolloid adsorbent. Unlike Example 1, the magnetic nanocores in this embodiment are prepared by a solvothermal method, and oxygen vacancies and some coordination unsaturated sites are formed in situ during particle formation by utilizing the weak reducing environment and non-stoichiometric control of the solvothermal system itself; at the same time, the amphiphilic bio-based colloidal network is constructed by a blending crosslinking method.
[0065] S1. Preparation of magnetic nanonuclei 4.86 g of ferric chloride hexahydrate and 0.42 g of manganese acetylacetone were weighed and added to a mixed solvent prepared by ethylene glycol and deionized water at a volume ratio of 4:1, with a total solvent volume of 180 mL. Then, 6.0 g of sodium acetate and 1.2 g of polyvinylpyrrolidone (PVP, K30) were added, and the mixture was magnetically stirred at room temperature for 40 min to form a uniform brownish-yellow precursor solution. The molar ratio of iron to manganese was 92:8.
[0066] The obtained precursor solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 190°C for 10 hours. Ethylene glycol, acting as both a solvent and a weak reducing agent under high-temperature conditions, can promote Fe crystallization during the particle crystallization process. 2+ / Fe 3+ They coexist and induce the formation of a certain number of oxygen vacancies and coordination unsaturated sites.
[0067] After the reaction was completed, the mixture was naturally cooled to room temperature and then magnetically separated using an external magnetic field. The resulting precipitate was washed three times with anhydrous ethanol and deionized water, and then vacuum dried at 60°C for 10 h to obtain Mn-doped composite ferrite magnetic nanoparticles.
[0068] Transmission electron microscopy revealed that the average particle size of the obtained magnetic nanonuclei was approximately 28 nm; the saturation magnetization was 74 emu / g, as measured by a vibrating sample magnetometer.
[0069] S2. Preparation of colloidal precursors Weigh 2.5g of chitosan and add it to 100mL of 2wt% acetic acid solution, stirring at 50℃ until completely dissolved; separately weigh 1.5g of sodium lignosulfonate and add it to 80mL of deionized water, stirring to dissolve. Then mix the two solutions and continue stirring for 30min to form a bio-based polymer mixture system.
[0070] A pre-prepared hydrophobic polymer emulsion is added, wherein the hydrophobic grafted polymer is a lauryl acrylate-methyl methacrylate copolymer emulsion with a solid content of 30 wt% and an addition amount of 35 wt% of the total mass of the bio-based polymer.
[0071] Add 0.8 mL of glutaraldehyde aqueous solution (25 wt%) as a crosslinking agent, and continue stirring at room temperature for 20 min to form an amphiphilic colloidal precursor.
[0072] S3, Composite Molding The Mn-doped composite ferrite magnetic nanoparticles obtained in S1 are added to the amphiphilic colloidal precursor obtained in S2, such that the ferrite-type composite magnetic nanoparticles account for 40 wt% of the total solid mass of the magnetic nanocolloid adsorbent.
[0073] Subsequently, a high-shear emulsifier was used to disperse the magnetic nanonuclei at 1800 rpm for 12 min, so that the magnetic nanonuclei were uniformly dispersed in the colloidal system.
[0074] After dispersion, a blending and crosslinking reaction was carried out at 45℃ for 4 hours. During the crosslinking process, the amino groups in chitosan and the aldehyde groups in glutaraldehyde undergo Schiff base reaction, while sodium lignosulfonate and chitosan form hydrogen bonds and molecular chain entanglement. The hydrophobic polymer segments are embedded in the colloidal network through hydrophobic association, thereby forming a stable amphiphilic bio-based colloidal network and encapsulating the magnetic nanonucleus inside the network.
[0075] S4, Post-processing The obtained magnetic nanocolloid composite was washed three times with an ethanol / deionized water mixture to remove residual crosslinking agent and free low molecular weight substances; then it was vacuum dried at 50°C for 12 h to obtain the magnetic nanocolloid adsorbent.
[0076] Results and Performance The resulting material is a dark brown, loose, granular substance with good magnetic responsiveness and oil-phase spreading ability. In a simulated marine lubricating oil seawater spill system, the material can quickly adhere to the oil film surface and disturb the interfacial aggregation structure in the emulsified lubricating oil, causing the oil droplets to gradually coalesce. After adsorption, it can achieve rapid aggregation and recovery under an applied magnetic field of 0.08T.
[0077] Example 3:
[0078] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Co-doped system, wherein the molar ratio of Fe to Co is adjusted to 93:7; the low-temperature heat treatment conditions in step S1 are adjusted to 220°C for 1.5h under an argon atmosphere.
[0079] In step S2, the bio-based polymer is adjusted to a combination of chitosan and oxidized cellulose; the hydrophobic grafted polymer is adjusted to a methacrylate polymer containing C12 alkyl side chains.
[0080] In step S3, the in-situ polymerization temperature is adjusted to 70℃ and the polymerization time is 5h.
[0081] The obtained magnetic nanonuclei have an average particle size of approximately 35 nm and a saturation magnetization of approximately 91 emu / g.
[0082] Example 4:
[0083] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Cu doping system, wherein the molar ratio of Fe to Cu is adjusted to 95:5; the low-temperature heat treatment conditions in step S1 are adjusted to be treated at 180°C for 3 hours under a nitrogen atmosphere.
[0084] In step S2, the bio-based polymer is adjusted to be a combination of carboxymethyl cellulose and tannic acid derivatives; the hydrophobic grafted polymer is adjusted to be an acrylate polymer containing C16 alkyl side chains.
[0085] In step S3, the ferrite-type composite magnetic nanoparticles account for 50 wt% of the total solid mass of the magnetic nanocolloid adsorbent and are dispersed under high shear at 3000 rpm for 10 min.
[0086] The average particle size of the obtained magnetic nanonuclei is about 31 nm, and the saturation magnetization is about 84 emu / g.
[0087] Example 5:
[0088] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Ni-doped system, wherein the molar ratio of Fe to Ni is adjusted to 90:10; the low-temperature heat treatment conditions in step S1 are adjusted to be 200°C for 2 hours under a reducing atmosphere.
[0089] In step S2, the bio-based polymer is adjusted to be a combination of lignin derivatives and chitosan; the hydrophobic grafted polymer is adjusted to be a polyurethane acrylate polymer.
[0090] In step S3, the in-situ polymerization temperature is adjusted to 80℃ and the polymerization time is 2h.
[0091] The obtained magnetic nanonuclei have an average particle size of approximately 27 nm and a saturation magnetization of approximately 76 emu / g.
[0092] Example 6:
[0093] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Mn doping system, wherein the molar ratio of Fe to Mn is adjusted to 92:8; the low-temperature heat treatment conditions in step S1 are adjusted to be treated at 210°C for 2 hours under a nitrogen atmosphere.
[0094] In step S2, the bio-based polymer is adjusted to be a combination of starch derivative and carboxymethyl cellulose; the hydrophobic grafted polymer is adjusted to be a methacrylate polymer containing C8-C18 alkyl side chains.
[0095] In step S3, the mass ratio of the bio-based polymer to the hydrophobic grafted polymer is adjusted to 100:80.
[0096] The obtained magnetic nanonuclei have an average particle size of approximately 42 nm and a saturation magnetization of approximately 69 emu / g.
[0097] Example 7:
[0098] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Co / Ni composite doping system, wherein the molar ratio of Fe to the total metal elements of Co and Ni is adjusted to 91:9.
[0099] In step S2, the bio-based polymer is adjusted to be a combination of oxidized cellulose and lignin derivatives; the hydrophobic grafted polymer is adjusted to be an acrylate polymer containing C18 alkyl side chains.
[0100] In step S3, the ferrite-type composite magnetic nanoparticles account for 35 wt% of the total solid mass of the magnetic nanocolloid adsorbent and are dispersed under high shear at 1500 rpm for 20 min; the in-situ polymerization temperature is 65℃ and the polymerization time is 6 h.
[0101] The obtained magnetic nanonuclei have an average particle size of approximately 38 nm and a saturation magnetization of approximately 88 emu / g.
[0102] Example 8:
[0103] Based on Example 1, the composite ferrite nanoparticles in step S1 adopt a Mn / Cu composite doping system, wherein the molar ratio of Fe to the total metal elements of Mn and Cu is adjusted to 94:6.
[0104] In step S2, the bio-based polymer is adjusted to be a combination of tannic acid derivatives and starch derivatives; the hydrophobic grafted polymer is adjusted to be a polyurethane acrylate polymer.
[0105] In step S3, the ferrite-type composite magnetic nanoparticles account for 60 wt% of the total solid mass of the magnetic nanocolloid adsorbent and are dispersed under high shear at 2000 rpm for 15 min; the in-situ polymerization temperature is 85℃ and the polymerization time is 1 h.
[0106] The obtained magnetic nanonuclei have an average particle size of approximately 24 nm and a saturation magnetization of approximately 72 emu / g.
[0107] Comparative Example 1: Basic complex without defect regulation and without the introduction of hydrophobic grafting network.
[0108] The above embodiments were tested to verify their performance. 1. The lubricating oil adsorption capacity of Examples 1-3, 5 / 8 and Comparative Example 1 was compared, and the results are shown in Table 1:
[0109] 2. The demulsification effect of emulsified lubricating oil is shown in Table 2 below:
[0110] 3. Rheological viscosity reduction effect, the results are shown in Table 3 below:
[0111] 4. The magnetic recovery effect is shown in Table 4 below:
[0112] As can be seen from the table, Example 1 exhibits the best overall performance. It has the highest adsorption capacity, the fastest demulsification rate, the most significant viscosity reduction rate, and the highest magnetic recovery efficiency, indicating that the combination of co-precipitation preparation of magnetic cores, low-temperature heat treatment for defect control, and in-situ polymerization to construct an amphiphilic network is the most reasonable.
[0113] Example 3 showed the best magnetic recovery performance, indicating that the Co-doped system has a greater advantage in maintaining a high magnetic response and is suitable for scenarios with high recovery speed requirements.
[0114] Example 2 showed good demulsification and adsorption performance, indicating that the formation of defect sites by the solvothermal method is also beneficial to the disturbance of the lubricating oil interface film and the enrichment of the oil phase.
[0115] The overall performance of Examples 5 and 8 is slightly lower, but still significantly better than the comparative examples, indicating that Ni-doped and Mn / Cu composite doped systems can also meet the requirements for marine oil spill treatment, although the magnetic response and interfacial interaction are slightly weaker than those of Examples 1 and 3.
[0116] Comparative Example 1 showed significantly worse performance across all aspects, demonstrating that the synergistic structure of defect regulation, hydrophobic graft network, and ferrite composite magnetic core is key to achieving efficient adsorption, demulsification, viscosity reduction, and magnetic recovery.
[0117] In summary, the magnetic nanocolloid adsorbent of the present invention exhibits high adsorption capacity, fast demulsification rate, significant viscosity reduction effect, and excellent magnetic recovery performance for marine oil spills of lubricating oil. Among them, Example 1 shows the best overall effect, while Example 3 has a greater advantage in magnetic recovery performance. This demonstrates that the present invention, through the synergistic design of ferrite composite magnetic core, amphiphilic bio-based colloidal network, and defect site regulation, can effectively adapt to the complex interface characteristics of lubricating oil spills.
[0118] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A magnetic nanocolloid adsorbent, characterized in that, It includes a magnetic nanocore and an amphiphilic bio-based colloidal network coated on the surface of the magnetic nanocore; The ferrite-type composite magnetic nanoparticles are selected from at least one of Fe3O4 or γ-Fe2O3, and the ferrite-type composite magnetic nanoparticles are doped with at least one metal element selected from Co, Ni, Mn and Cu, and the molar ratio of Fe to the metal element is 95:5 to 90:
10. The amphiphilic bio-based colloidal network is formed by in-situ polymerization or blending and cross-linking of bio-based polymers and hydrophobic grafted polymers; The bio-based polymer is selected from at least one of chitosan, carboxymethyl cellulose, oxidized cellulose, lignin derivatives, tannic acid derivatives, and starch derivatives; The hydrophobic grafted polymer is selected from at least one of acrylate polymers containing C8-C18 alkyl side chains, methacrylate polymers, and polyurethane acrylate polymers; The magnetic nanonucleus accounts for 35-70 wt% of the total mass of the magnetic nanocolloid adsorbent, with the remainder being amphiphilic bio-based colloidal components.
2. The magnetic nanocolloid adsorbent according to claim 1, characterized in that, The magnetic nanonuclei have an average particle size of 10–80 nm.
3. The magnetic nanocolloid adsorbent according to claim 1, characterized in that, The saturation magnetization of the magnetic nanonucleus is 40–180 emu / g.
4. The magnetic nanocolloid adsorbent according to claim 1, characterized in that, In the amphiphilic bio-based colloidal network, the mass ratio of the bio-based polymer to the hydrophobic grafted polymer is 100:(10-80).
5. A method for preparing the magnetic nanocolloid adsorbent according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Preparation of magnetic nanonuclei: Combine an iron source with at least one of a Co source, Ni source, Mn source, or Cu source, and obtain composite ferrite nanoparticles by at least one of a co-precipitation method, a hydrothermal method, or a solvothermal method. S2. Preparation of colloidal precursor: Bio-based polymers are mixed with hydrophobic grafted polymers, and crosslinking agents and / or initiators are added to form amphiphilic colloidal precursors; S3. Composite molding: The composite ferrite nanoparticles are added to the amphiphilic colloidal precursor, and magnetic nanocolloid composites are prepared by in-situ polymerization or blending. S4. Post-processing: The magnetic nanocolloid composite is washed, cured and dried to obtain the magnetic nanocolloid adsorbent.
6. The method for preparing a magnetic nanocolloid adsorbent according to claim 5, characterized in that, The iron source mentioned in step S1 includes Fe 2+ Salt and Fe 3+ At least one of the salts, the Fe 2+ Salt and Fe 3+ The salt is selected from at least one of chloride, sulfate, and nitrate; the Co source, Ni source, Mn source, and Cu source are selected from at least one of their corresponding chloride, sulfate, and nitrate.
7. The method for preparing a magnetic nanocolloid adsorbent according to claim 5, characterized in that, In step S2, the bio-based polymer has a mass fraction of 1–8 wt%, the hydrophobic grafted polymer has a mass fraction of 2–20 wt%, the crosslinking agent has a mass fraction of 0.2–5 wt%, and the initiator has a mass fraction of 0.1–2 wt%.
8. The method for preparing a magnetic nanocolloid adsorbent according to claim 5, characterized in that, In step S3, the ferrite-type composite magnetic nanoparticles account for 35-60 wt% of the total solid mass of the magnetic nanocolloid adsorbent and are dispersed under high shear at 500-3000 rpm for 5-30 min.
9. The application of a magnetic nanocolloid adsorbent in marine oil spill treatment, characterized in that, The spilled oil is of the lubricating oil type, which includes at least one of engine lubricating oil, gear oil, hydraulic oil, marine lubricating oil, and industrial grease spilled oil.
10. The application of a magnetic nanocolloid adsorbent according to claim 9 in marine oil spill treatment, characterized in that, The lubricating oil comprises a base oil and an additive system, wherein the additive system includes at least one of detergent-dispersant, antioxidant, extreme pressure agent, anti-wear agent, and metal passivator.
